Avaliação do efeito do ácido ascórbico (vitamina C) como antioxidante no polietileno de ultra alta massa molar (UHMWPE) - Souza, Vanessa Castro de (2013)
The current work aims at investigate the effect of incorporation of a new antioxidant vitamin C(ascorbic acid) in ultrahigh molecular weight polyethylene (UHMWPE) matrix from thermooxidation perspective. Ultrahigh molecular weight polyethylene/vitamin C) blends, with different vitamin C contents (0.5, 1 and 2 wt%) were prepared via compression molding technique, have been investigated using several analytical steps (SEM, DSC, TG, FTIR and antioxidant activity). Thermal degradation behavior of neat UHMWPE and its blends were estimated using the Friedman, the Ozawa, Flynn, and Wall (OFW) methods. Results indicated that the polymer/vitamin C blends have homogeneous morphology. The addition of ascorbic acid seems to have no influence in crystallization and melting properties of the polymer. Moreover, the antioxidant activity of Vitamin C remained in their mixtures with UHMWPE. The analysis of the fracture surface of UHMWPE / vitamin C showed that there was no adhesion between the phases and Spectroscopy results do not show chemical interaction between UHMWPE and vitamin C. In addition, vitamin C was effective to secure the thermal performance of UHMWPE, especially when added at a concentration of 1%wt, it´s increasing the activation energy (Ea) of UHMWPE without changing its profileof reaction order (n).